Keratose‐dominated sponge grounds from temperate mesophotic ecosystems (NW Mediterranean Sea). (25th October 2020) - Enrichetti, Francesco; Bavestrello, Giorgio; Betti, Federico; Coppari, Martina; Toma, Margherita; Pronzato, Roberto; Canese, Simonepietro; Bertolino, Marco; Costa, Gabriele; Pansini, Maurizio; Bo, Marzia
Abstract: Differently from the North Atlantic Ocean, only few examples of sponge grounds are known from the Mediterranean Sea, mainly thriving in the deep sea. In this study, a novel temperate mesophotic ecosystem dominated by massive keratose sponges is reported from the Ligurian deep continental shelf. An extensive Remotely Operated Vehicle (ROV) survey allowed to study the structure and large‐scale distribution of this biocoenosis. The sponge grounds here described are highly fragmented, being formed by a large number of dense, discrete aggregations of Sarcotragus foetidus (up to 7.7 specimens/m 2 ) and other sponges, including Spongia lamella and Axinella polypoides . They mainly occur on flat, patchy and highly silted hardgrounds between 40 and 70 m depth. These sponge‐dominated ecosystems have an exceptionally wide spatial distribution, estimated to cover up to nearly 200 hectares, with the largest sponge grounds occurring along the westernmost part of the Ligurian coast, probably in relation to more suitable oceanographic conditions. The dominant sponge species reach considerable heights (up to 65 cm), greatly increasing the habitat three‐dimensionality and acting as poles of attraction for a diverse sessile and vagile fauna. In addition, the high abundance of the keratose sponge grounds at mesophotic depths might represent a larval source for shallow‐water populations that in the last decades have been stricken by several mass mortality events.